The strangers in our midst: American evangelicals and immigration from the Cold War to the twenty-first century - Stockhausen, Ulrike Elisabeth (Oxford scholarship online, 2021)
Evangelical Christians in the United States today are known for their hard-line, restrictive approach to immigration and refugees insofar that means welcoming immigrants and refugees into the country. This book shows that this has not always been the case and is, in fact, a relatively new position. The history of evangelical involvement with refugees and immigrants has been overlooked in the current debate. Since the early 1960s, evangelical Christians have been integral players in US immigration and refugee policy. Motivated by Biblical teachings to 'welcome the stranger,' they have helped tens of thousands of newcomers by acting as refugee sponsors or providing legalization assistance to undocumented immigrants. Until the 1990s, many evangelicals did not distinguish between documented and undocumented newcomers - all were to be loved and welcomed.